CONTRADICTIONS IN SERVICE CHARTERS IN INDONESIA: A BIBLIOMETRIC ANALYSIS AND SYSTEMATIC LITERATURE REVIEW - Yuliansah, Romi Ali; Pratama, Dendi Pribadi (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
his research applies a mixed-method design through Bibliometric Analysis and Systematic Literature Review (SLR). The bibliometric analysis was conducted using VOSViewer, and data were collected from 836 articles published between 2000 and 2024 through the Google Scholar database. The systematic review was managed using Covidence to filter, extract, and synthesize relevant literature. The collected articles were classified into three groups: international journals, indexed international journals, and national journals, with the majority (62%) originating from indexed international publications. The findings show that research on service charters in Indonesia is still fragmented and rarely integrates the three analytical dimensions: service charters, organizational effectiveness, and service evaluation. The bibliometric mapping reveals that recent studies increasingly emphasize “service standards,” “performance measurement,” and “organizational improvement,” yet lack comprehensive evaluation frameworks. This study concludes that the implementation of service charters in Indonesia requires more vigorous policy enforcement, continuous evaluation, and institutional commitment to ensure tangible improvement in public service performance. The research contributes a novel analytical framework combining bibliometric mapping and systematic synthesis to enrich theoretical and empirical understanding of service charters in the context of public administration.